2017
DOI: 10.17126/joralres.2017.036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of platelet rich fibrin in the treatment of periodontal intrabony defects. Systematic review and meta-analysis.

Abstract: Background: There is currently no gold standard biomaterial for the treatment of periodontal intrabony defects (PIDs). One of the current options is the use of platelet-rich fibrin (PRF). Objective: To determine the clinical effect of PRF in the treatment of PID through a systematic review and meta-analysis. Materials and Methods: A literature search was conducted up to February 2017 in the following biomedical databases: Pubmed, Embase, Scielo, Science Direct, SIGLE, LILACS and in the Cochrane Central Registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 1 publication
1
6
2
Order By: Relevance
“…In a systematic review involving the adjunctive use of PRP, no significant differences were found between the two study designs . This supports a recent systematic review where a meta‐epidemiological study showed no difference between parallel and split‐mouth designs in continuous and binary data . In contrast, Hou et al stated: “different study designs are not equally effective in assessing the clinical efficacy of PRP”.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In a systematic review involving the adjunctive use of PRP, no significant differences were found between the two study designs . This supports a recent systematic review where a meta‐epidemiological study showed no difference between parallel and split‐mouth designs in continuous and binary data . In contrast, Hou et al stated: “different study designs are not equally effective in assessing the clinical efficacy of PRP”.…”
Section: Discussionsupporting
confidence: 56%
“…The present review was limited by the methodological detail provided in the published papers; for example, in the paper by Josephi et al, the blinding methods of the participants was unclear. Moreover, a recent systematic review reported that two the of four appraised papers had allocation concealment, whereas the methodology in the respective papers did not demonstrate this. If the information in the systematic review, which was not indexed in the CENTRAL database, was incorrect, the authors approached each researcher to further discuss their methodology.…”
Section: Discussionmentioning
confidence: 98%
“…Periodontitis is a chronic infectious disease that causes damage to periodontal tissues. [ 1 ] One of its consequences is alveolar bone resorption, which generates horizontal or vertical bone defects and supra- or intrabony defects, causing mobility and tooth loss. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several current clinical trials and systematic reviews that compare OFD plus PRF with OFD alone have indicated benefits for clinical attachment level (CAL) gain, decreased probing depth (PD), reduction, or filling of the bony defect. [ 1 , 2 , 8 - 10 , 13 - 18 ] However, this evidence is still unclear since the fast scientific progress in periodontics on regenerative treatments have led to different conclusions on the most effective treatment for patients with intrabony defects. Likewise, many periodontic specialists continue to use periodontal regenerative treatments with different biodegradable materials of synthetic and animal origin, not considering that these biomaterials have a higher risk of infection, hypersensitivity reactions, and poor biomechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation